Frequency and Spectrum of KRAS Mutations in Moroccan Patients with Lung Adenocarcinoma. (4th March 2014) - Elghissassi, Ibrahim; Inrhaoun, Hanane; Boukir, Anwar; Kettani, Fouad; Gamra, Lamia; Mestari, Amina; Jabri, Lamia; Bensouda, Youssef; Mrabti, Hind; Errihani, Hassan
Abstract : Background . In lung adenocarcinoma, the frequency of KRAS mutations is ethnicity dependent with a higher proportion in African Americans and white Caucasians than in Asians. The prevalence of these mutations among North Africans patients is unknown. The objective of this study was to report the frequency and spectrum of KRAS mutations in a group of Moroccan lung adenocarcinoma patients. Methods . Tumor specimens from 117 Moroccan patients with lung adenocarcinoma were selected to determine frequency and spectrum of KRAS mutations. KRAS mutations in codons 12 and 13 of exon 2 were analyzed using conventional DNA sequencing. Results . The overall frequency of the KRAS mutations was 9% (11/117). In the population with KRAS mutations, there was a trend towards more male (P = 0.06 ) and more smokers (P = 0.08 ) compared to patients with wild type KRAS. KRAS mutations were located at codon 12 in 10 out of 11 patients (91%). The G12C mutation was the most frequent KRAS mutation (73%). Conclusion . This is the first study to date examining the frequency and spectrum of KRAS mutations in lung adenocarcinomas in North African and Arab populations. KRAS mutation frequency in Moroccan patients was comparable with the frequency observed in East-Asian population. KRAS mutations are more likely observed in males and smokers and to be transversions. Further studies, in larger numbers of patients, are needed to confirm these findings.